Functions of deixists and delimiters in the language of literary text - Mukhamejanova А.Т.; Mukhamejanova Г.Т.; Tolysbayeva Ж.Ж. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
This article explores the structural and semantic functions of pragmatic devices that ensure textual cohesion in literary discourse, specifically deixis and discourse markers. The study focuses on the specific features of deictic and discourse-marker constructions in Baurzhan Momyshuly’s autobiographical novel "Ushqan uya". ("Our Family"). Drawing on linguistic, pragmatic, cognitive, and stylistic approaches, the paper reveals the role of deictic elements in establishing referential connections within the text and the function of discourse markers in generating logical and emotional relations. Particular attention is given to the use of personal, temporal, and spatial deixis, with illustrative examples demonstrating how these devices construct interaction between the reader and the narrative. The analysis also addresses how discourse markers encode causal, contrastive, and affective relations across sentence boundaries. The findings contribute to a deeper understanding of cohesion and pragmatic impact in Kazakh literary discourse and may serve as a basis for further research in text linguistics, discourse pragmatics, and cohesive analysis of literary texts.